Effects of indiscriminate fisheries on a group of small data-poor species in Thailand - Aylesworth, Lindsay; Phoonsawat, Ratanavaree; Vincent, Amanda C J (ICES journal of marine science, 2018)
Abstract As catches of economically valuable target fishes decline, indiscriminate fisheries are on the rise, where commercial and small-scale fishers retain and sell an increasing number of marine species. Some of these catches are destined for international markets and subject to international trade regulations. Many of these species are considered “data-poor” in that there are limited data on their biology, ecology, and exploitation, which poses a serious management challenge for sustainable fisheries and trade. Our research explores the relative pressure exerted by such indiscriminate fisheries on a data-poor marine fish genus—seahorses (Hippocampus spp.)—whose considerable international trade is regulated globally. Our focus is Thailand, a dominant fishing nation and the world‘s largest exporter of seahorses, where we gathered data by interviewing commercial and small-scale fishers and through port sampling of landed catch. We estimate that annual catches were more than threefold larger than previously documented, approximating 29 million individuals from all gears. Three fishing gears–two commercial (otter and pair trawl) and one small-scale (gillnet)–caught the most individuals. Results from port sampling and our vulnerability analysis confirmed that H. kelloggi, H. kuda, and H. trimaculatus were the three species (of seven found in Thai waters) most susceptible to fishing. Small-scale gillnets captured the majority of specimens under length at maturity, largely due to catches of juvenile H. kuda and H. trimaculatus. This research indicates a role for vulnerability analysis to initiate precautionary management plans while more extensive studies can be conducted.